Prinsip Pemuridan dalam Pendidikan Agama Kristen dan Implementasinya Pada Remaja di Era Digital - Candra Nugraha Wati (LPPM STT Baptis Kalvari, 2022)
Discipleship is a form of service that the Lord Jesus did while on earth. There is an educational process in it that focuses on God's Word. Disciples are taught the truth of God's Word and to apply it in all aspects of their lives so that they grow in the character of Christ. Youth ministry is a form of Christian religious education. Teenagers are taught the principles of the truth of God's Word in facing the challenges of rapid technological development in this digital era. Families, schools, and churches as educational institutions have an important role in Christian religious education for adolescents. This is qualitative research with a literature study method. The purpose of this study is to examine the principle of discipleship in Christian religious education and its implementation in adolescents in the digital era. The result of this research is the principle of discipleship in Christian religious education is evangelism and coaching. The implication for teenagers is that it can be done by building closeness with teenagers in friendship, providing life examples, and guiding them to live God's Word in this digital era.